A visual semiotic analysis of sperm donors' baby photos as major marketing material at the s[u]permarket. (May 2017) - Bokek-Cohen, Ya'arit
This article presents a semiotic visual analysis of 48 sperm donors' baby photos from six of the largest American sperm banks, using Kress and Van Leeuwen's method of 'reading images' described in Reading Images: The Grammar of Visual Design (2006). Donor baby photos, conceptualized as self-advertisements, serve to engage prospective sperm users because of their liminal nature. The following issues are addressed: How do sperm donors use baby photos to transmit messages to prospective recipients? What are the cultural values conveyed via the photos? Is there a correspondence between donors' verbal narratives and meanings encoded in baby photos? Furthermore, a new category of 'chosen/selected' images is proposed for classifying photos that were neither made for the purpose of the study nor found by the researcher. The photo selection is strategic and serves to engage sperm recipients in imaginary relations with donors. Furthermore, subversive messages tacitly transmitted in baby photos desemiotize some of the stated values in the verbal narratives.